2016
DOI: 10.3390/insects7040072
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Effect of Zeolites on the Tomato Leafminer Tuta absoluta (Lepidoptera: Gelechiidae)

Abstract: (1) Background: The tomato leafminer Tuta absoluta (Lepidoptera: Gelechiidae) is a key tomato insect pest. At present, it is considered to be a serious threat in various countries in Europe, North Africa, and Middle East. The extensive use and the developed resistance of T. absoluta to spinosad causes some concern, which leads to the need for alternative products. (2) Materials and Methods: Several laboratory experiments were conducted to investigate the ovicidal properties of a zeolite particle film on T. abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…The consumed cabbage with the formulation was ingested by the larvae and firstly, the nanozeolite particles were absorbed by larval midgut and then the polyhedra directly entered the larval midgut lead to infection of the larval body cells. This phenomenon was also reported that the use of zeolites accelerated the lethal time in Tuta absoluta and as a result absorbed the liquid in the insect's body (De Smedt et al, 2016). In this study, the use of HaNPV 1 tailored with a delivery system of nanozeolite was effective in accelerating the lethal time and significantly enhanced the mortality against C. pavonana larvae.…”
Section: Treatmentsupporting
confidence: 62%
See 1 more Smart Citation
“…The consumed cabbage with the formulation was ingested by the larvae and firstly, the nanozeolite particles were absorbed by larval midgut and then the polyhedra directly entered the larval midgut lead to infection of the larval body cells. This phenomenon was also reported that the use of zeolites accelerated the lethal time in Tuta absoluta and as a result absorbed the liquid in the insect's body (De Smedt et al, 2016). In this study, the use of HaNPV 1 tailored with a delivery system of nanozeolite was effective in accelerating the lethal time and significantly enhanced the mortality against C. pavonana larvae.…”
Section: Treatmentsupporting
confidence: 62%
“…It is also reported the similar phenomena that zeolite kills insects mainly by abrasive action or by absorption of epicuticular lipids from the insect exoskeleton causing excessive dehydration (Lu et al, 2017). Also, zeolites work by creating a barrier film by covering the leaves with a white powdery film, which adheres and irritates insects (De Smedt et al, 2016).…”
Section: Treatmentmentioning
confidence: 92%
“…Desiccant activity, resulting from the active surfaces with water sorption capacity and large volumes of pores and interconnected nanotunnels, is responsible for the activity against plant pathogens and pests from stored grains [3] or leaves [11]. Large volumes of free space and active surfaces, with cation exchange capacity and/or polarized molecules, are involved in the improving effects of SNNMs on soils or growing media [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…11 On the contrary, it was revealed that the number of eggs laid by T. absoluta females on the treated leaves did not differ significantly from the control, with the exception of leaves treated with zeolits. 12 T. parthenium and T. vulgare are medicinal plants. There are many studies on the effect of T. parthenium and T. vulgare extracts on other insects.…”
Section: Resultsmentioning
confidence: 99%